2012
DOI: 10.1186/1471-2164-13-615
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the spalax hypoxia survival response includes suppression of apoptosis and tight control of angiogenesis

Abstract: BackgroundThe development of complex responses to hypoxia has played a key role in the evolution of mammals, as inadequate response to this condition is frequently associated with cardiovascular diseases, developmental disorders, and cancers. Though numerous studies have used mice and rats in order to explore mechanisms that contribute to hypoxia tolerance, these studies are limited due to the high sensitivity of most rodents to severe hypoxia. The blind subterranean mole rat Spalax is a hypoxia tolerant roden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 57 publications
4
48
0
Order By: Relevance
“…S3). In a previous RNA-Seq Spalax brain microarray study22, these ECM related terms were significantly overrepresented among hypoxia responsive genes, and were part of a cluster of functionally-related terms associated with hypoxia-induced angiogenesis.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…S3). In a previous RNA-Seq Spalax brain microarray study22, these ECM related terms were significantly overrepresented among hypoxia responsive genes, and were part of a cluster of functionally-related terms associated with hypoxia-induced angiogenesis.…”
Section: Resultsmentioning
confidence: 79%
“…The Spalax genome was recently sequenced21, and Spalax normoxia vs. hypoxia genome-wide molecular responses were explored in both brain and muscle tissues2122. These studies revealed the involvement of multiple functional groups of genes in the hypoxia-induced responses of Spalax .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy are VEGF , constitutively highly expressed as compared to rats [7]; p53 that harbors substitutions in the DNA-binding site, identical to the most common p53 mutations in tumors; however, in Spalax it renders a bias against apoptosis but favors cell cycle arrest/DNA repair both in vitro and in vivo [8]; and a unique Spalax heparanase splice variant that was shown to decrease tumor size in mice by a factor of 7 and reduce metastatic activity compared to native mice heparanase [9]. Furthermore, assessment of Spalax transcriptome assembly and expression data has revealed enrichment of genes that overlap cancer resistance, apoptosis, angiogenesis pathways and hypoxia-tolerance [10,11]. This suggests that Spalax is potentially resistant to malignant transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxic conditions regulate gene transcription in cellular responses to promote metabolism and angiogenesis through adaptive processes (13)(14)(15)(16). Accordingly, modulation of gene transcription through HIF-1 plays an important role in hypoxia for cell survival (17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%